2012
DOI: 10.1016/j.tjog.2012.01.011
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of nerve-sparing radical hysterectomy for uterine cervical carcinoma in Taiwan

Abstract: We concluded that the new technique of NRH can reduce postoperative bladder dysfunctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…In the end, 17 studies were included in the meta-analysis (Figure 1), including 13 involving laparotomy [21][33] and 4 involving laparoscopy [34]–[37]. Of these 17, 10 were conducted in mainland China [24], [25], [28], [29], [31], [32], [34]–[37], one in Taiwan [33], two in Japan [21], [23], two in Italy [22], [30], one in Poland [27] and one in the Netherlands [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the end, 17 studies were included in the meta-analysis (Figure 1), including 13 involving laparotomy [21][33] and 4 involving laparoscopy [34]–[37]. Of these 17, 10 were conducted in mainland China [24], [25], [28], [29], [31], [32], [34]–[37], one in Taiwan [33], two in Japan [21], [23], two in Italy [22], [30], one in Poland [27] and one in the Netherlands [26].…”
Section: Resultsmentioning
confidence: 99%
“…Of these 17, 10 were conducted in mainland China [24], [25], [28], [29], [31], [32], [34]–[37], one in Taiwan [33], two in Japan [21], [23], two in Italy [22], [30], one in Poland [27] and one in the Netherlands [26]. One study included three groups [22], so we extracted only the data for the Type III NSRH group and the Type III RH group.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13][14][26][27][28][29] Most of these comparison studies had a small sample size (\50 patients with NSRH). [10][11][12]26,27,29 However, the groups in the larger studies also were mostly noncomparable for several reasons: (1) two of the largest trials used historical cohorts 14,28 ; (2) in one study, only patients with worse prognostic factors were referred to CRH 13 ; and (3) in another relatively larger study, the adjuvant treatment strategy of the study cohorts was not clearly identified. 19 Moreover, only three comparison trials 13,14,28 reported the effect estimates of NSRH, which were few and heterogeneous and thus precluded a standard meta-analysis or weighted pooling of results due to a severe risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…16 Thus, we were able to find seven retrospective studies focused mainly on oncologic outcomes of NSRH. 11,13,14,17,23,24,28 Outcomes Our literature search found heterogeneous oncologic outcomes ranging from no overall recurrences 15,17,19,20,22,25,27,29 to an overall recurrence rate of 19.6 % 28 after NSRH.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation